Reliability of Stress - Strength and Its Estimation of Exponentiated Q-Exponential Distribution - Jalal, Mohammed. S.; Batah , Feras Sh. M. (Iraqi Journal of Science, 2023)
In this paper, we study a single stress-strength reliability system , where Ƹ and ƴ are independently Exponentiated q-Exponential distribution. There are a few traditional estimating approaches that are derived, namely maximum likelihood estimation (MLE) and the Bayes (BE) estimators of R. A wide mainframe simulation is used to compare the performance of the proposed estimators using MATLAB program. A simulation study show that the Bayesian estimator is the best estimator than other estimation method under consideration using two criteria such as the “mean squares error (MSE)” and “mean absolutely error (MAPE)”.